Reverse lactate threshold: a novel single-session approach to reliable high-resolution estimation of the anaerobic threshold - Dotan, R. (International Journal of Sports Physiology and Performance, 2012)
The multisession maximal lactate steady-state (MLSS) test is the gold standard for anaerobic threshold (AnT) estimation. However, it is highly impractical, requires high fitness level, and suffers additional shortcomings. Existing single-session AnT-estimating tests are of compromised validity, reliability, and resolution. The presented reverse lactate threshold test (RLT) is a single-session, AnT-estimating test, aimed at avoiding the pitfalls of existing tests. It is based on the novel concept of identifying blood lactate`s maximal appearance- disappearance equilibrium by approaching the AnT from higher, rather than from lower exercise intensities. Rowing, cycling, and running case data (4 recreational and competitive athletes, male and female, aged 17-39 y) are presented. Subjects performed the RLT test and, on a separate session, a single 30-min MLSS-type verification test at the RLT-determined intensity. The RLT and its MLSS verification exhibited exceptional agreement at 0.5% discrepancy or better. The RLT`s training sensitivity was demonstrated by a case of 2.5-mo training regimen following which the RLT`s 15-W improvement was fully MLSS-verified. The RLT`s test-retest reliability was examined in 10 trained and untrained subjects. Test 2 differed from test 1 by only 0.3% with an intraclass correlation of 0.997. The data suggest RLT to accurately and reliably estimate AnT (as represented by MLSS verification) with high resolution and in distinctly different sports and to be sensitive to training adaptations. Compared with MLSS, the single-session RLT is highly practical and its lower fitness require- ments make it applicable to athletes and untrained individuals alike. Further research is needed to establish RLT`s validity and accuracy in larger samples.